2015
DOI: 10.1093/femspd/ftv063
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation of host-protective immune response by regulating Foxp3 expression and Treg function inLeishmania-infected BALB/c mice: critical role of IRF1

Abstract: Visceral leishmaniasis (VL), caused by a protozoan parasite Leishmania donovani, is still a threat to mankind due to treatment failure, drug resistance and coinfection with HIV. The limitations of first-line drugs have led to the development of new strategies to combat this dreaded disease. Recently, we have shown the immunomodulatory property of Ara-LAM, a TLR2 ligand, against leishmanial pathogenesis. In this study, we have extended our study to the effect of Ara-LAM on regulatory T cells in a murine model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…To ensure that sufficient T reg cells are present in the implantation area, their activation and proliferation during the preimplantation period are crucial. In the present study, some T reg -associated genes were found to be upregulated in SPtreated endometrium, including DLG1, FAS, LGALS1, STAT5A, and IRF1 in the uterine horn distal region (52)(53)(54)(55)(56). None of these genes or others associated with T reg cells were altered in the proximal uterine region.…”
Section: Discussioncontrasting
confidence: 39%
“…To ensure that sufficient T reg cells are present in the implantation area, their activation and proliferation during the preimplantation period are crucial. In the present study, some T reg -associated genes were found to be upregulated in SPtreated endometrium, including DLG1, FAS, LGALS1, STAT5A, and IRF1 in the uterine horn distal region (52)(53)(54)(55)(56). None of these genes or others associated with T reg cells were altered in the proximal uterine region.…”
Section: Discussioncontrasting
confidence: 39%
“…During viral infection, targeting EBI-3 led to cure (14). The suppressive activities of IL-10 (46, 47) and TGF-β (4850) and their contribution in murine VL are well established (51). Subsequently, Murray and colleagues proposed targeting IL-10 by neutralizing antibodies as a promising immunotherapy against murine VL (22, 46).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment with Ara‐LAM restricts L. donovani replication in target organs through mechanisms including improved CD8 + T‐cells recruitment and functions, enhanced Th1 responses, and suppressed T‐reg activity . Ara‐LAM also leads to the T‐bet induction, which activates effector CD8 + T‐cells that is reflected in the elevated expression of the IFN‐γ, granzyme‐B, perforin and in an NF‐κB and MAPK‐dependent process in VL (Figure ).…”
Section: The Functional Duality Of Tlr2 In Leishmaniasismentioning
confidence: 99%
“…It also modulates the IRF4 and IRF8 expression and reduces parasite burden in liver and spleen of BALB/c mice infected with L. donovani . Thus, the Ara‐LAM‐mediated improved IFN‐γ responsiveness is a novel principle that can be utilized to generate immunity against L. donovani in a susceptible host …”
Section: The Functional Duality Of Tlr2 In Leishmaniasismentioning
confidence: 99%